Evaluation of in Vivo Response of Three Biphasic Scaffolds for Osteochondral Tissue Regeneration in a Sheep Model - Alberto M. Crovace (Veterinary Sciences, 2019)
Osteochondral defects are a common problem in both human medicine and veterinary practice although with important limits concerning the cartilaginous tissue regeneration. Interest in the subchondral bone has grown, as it is now considered a key element in the osteochondral defect healing. The aim of this work was to generate and to evaluate the architecture of three cell-free scaffolds made of collagen, magnesium/hydroxyapatite and collagen hydroxyapatite/wollastonite to be implanted in a sheep animal model. Scaffolds were designed in a bilayer configuration and a novel “Honey” configuration, where columns of hydroxyapatite were inserted within the collagen matrix. The use of different types of scaffolds allowed us to identify the best scaffold in terms of integration and tissue regeneration. The animals included were divided into four groups: three were treated using different types of scaffold while one was left untreated and represented the control group. Evaluations were made at 3 months through CT analysis. The novel “Honey” configuration of the scaffold with hydroxyapatite seems to allow for a better reparative process, although we are still far from obtaining a complete restoration of the defect at this time point of follow-up.